Effective conductivity of 2D disk – ring composite material - Gryshchuk, Serhii; Rogosin, Sergei (Mathematical Modelling and Analysis, 2013)
For 2D bounded composite material geometrically composed by a disk of variable radius r and an outer ring it is determined in an analytic form the x-component of the effective conductivity tensor. Namely, it is shown that the x-component is a sum of geometrical progression with respect to powers of r 2 for all sufficiently small r.